1998
DOI: 10.1038/bjc.1998.366
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 mutations in southern England

Abstract: Summary If genetic testing for breast and ovarian cancer predisposition is to become available within a public health care system there needs to be a rational and cost-effective approach to mutation analysis. We have screened for BRCA 1 mutations in 230 women with breast cancer, all from the Wessex region of southern England, in order to establish the parameters on which to base a cost-effective regional mutation analysis strategy. Truncating mutations were detected in 10/155 (6.5%) consecutive cases selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 14 publications
2
26
0
2
Order By: Relevance
“…It thus seems on solid biochemical grounds to assume that BRCA1 and BRCA2 mutations predispose towards the development of bilateral breast cancer via their impairment of DNA repair. On the other hand, the first population-based studies of a limited number of BRCA1 and BRCA2 gene mutations have revealed mutations only in a small minority of patients with bilateral disease, and most of these also had an early onset at first primary (Eccles et al, 1998;Gershoni-Baruch et al, 1999).To gain more insight into the proportion of bilateral breast cancer that can be explained by BRCA1 and BRCA2 mutations in a hospital setting, we analysed the whole BRCA1 and BRCA2 coding region in 75 consecutive patients with bilateral breast cancer not selected for age or family history. Somewhat unexpectedly, only 5 unrelated carriers of a truncating mutation were identified.…”
mentioning
confidence: 99%
“…It thus seems on solid biochemical grounds to assume that BRCA1 and BRCA2 mutations predispose towards the development of bilateral breast cancer via their impairment of DNA repair. On the other hand, the first population-based studies of a limited number of BRCA1 and BRCA2 gene mutations have revealed mutations only in a small minority of patients with bilateral disease, and most of these also had an early onset at first primary (Eccles et al, 1998;Gershoni-Baruch et al, 1999).To gain more insight into the proportion of bilateral breast cancer that can be explained by BRCA1 and BRCA2 mutations in a hospital setting, we analysed the whole BRCA1 and BRCA2 coding region in 75 consecutive patients with bilateral breast cancer not selected for age or family history. Somewhat unexpectedly, only 5 unrelated carriers of a truncating mutation were identified.…”
mentioning
confidence: 99%
“…It was the most frequently recurring BRCA2 mutation (four examples) among 25 recorded by Gayther et al (1997) from 'the United Kingdom and Eire' but no further breakdown by geographical region was provided. BRCA1 4184 del4 was identified as a recurring mutation in that survey and also in separate reports of families from Wales and the South of England (Lancaster et al, 1998;Eccles et al, 1998). In the last-mentioned study, BRCA1 3875 was found five times in a total series of 17 mutations.…”
Section: Discussionmentioning
confidence: 78%
“…For BRCA1, two studies published in 1995 indicated that the relative risk of ovarian cancer was substantially higher for mutations occurring in the 5 0 two-thirds of the gene Shattuck-Eidens et al, 1995) but this was not confirmed in three other reports Couch et al, 1997;Frank et al, 1998) and is not apparent in a fourth (Eccles et al, 1998), where the data are presented but not discussed in detail. Taking the 3 0 end of exon 11 as the potential 'change point', we found a highly significant difference in the relative proportions of breast and ovarian cancers 'upstream' and 'downstream' of this position.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As there is uncertainty about many of the parameters associated with genetic breast cancer (Easton et al, 1993Ford et al, 1995;Couch et al, 1997;Serova et al, 1997;Stoppa-Lyonnet et al, 1997;Struewing et al, 1997;Whittemore et al, 1997;Eccles et al, 1998;Grann et al, 1999b), the uncertainty was accounted for by conducting one-way and multi-way sensitivity analysis upon the following model parameters:…”
Section: Sensitivity Analysismentioning
confidence: 99%